Electric network topology and method of transmission of electric energy - N. I. Smolentsev; L. M. Chetoshnikova (Известия высших учебных заведений: Проблемы энергетики)
The purpose of the work is to reduce losses and increase energy saving in electric networks. To achieve this goal, a multilevel topology of the electrical network and an asynchronous method for transferring electrical energy between nodes including a load, energy sources, energy storage devices connected in an appropriate manner are proposed. It is shown by the mathematical method that this network topology allows using energy storage devices controlled appropriately and using tele-information technologies to optimize the balance of electric energy in the network, achieving equality of the generated and consumed electricity. Such a network topology and a method of transmitting electrical energy can be the basis of digital technologies in the energy sector (ENERNET).